Enhancing cell and gene therapy manufacture through the application of advanced fluorescent optical sensors (Review) - Harrison, Richard P.; Chauhan, Veeren M. (AIP Publishing, 2018)
Cell and gene therapies (CGTs) are examples of future therapeutics that can be used to cure or alleviate the symptoms of disease, by repairing damaged tissue or reprogramming defective genetic information. However, despite the recent advancements in clinical trial outcomes, the path to widescale adoption of CGTs remains challenging, such that the emergence of a “blockbuster” therapy has so far proved elusive. Manufacturing solutions for these therapies require the application of scalable and replicable cell manufacturing techniques, which differ markedly from the existing pharmaceutical incumbent. Attempts to adopt this pharmaceutical model for CGT manufacture have largely proved unsuccessful. The most significant challenges facing CGT manufacturing are process analytical testing and quality control. These procedures would greatly benefit from improved sensory technologies that allow direct measurement of critical quality attributes, such as pH, oxygen, lactate and glucose. In turn, this would make manufacturing more robust, replicable and standardized. In this review, the present-day state and prospects of CGT manufacturing are discussed. In particular, the authors highlight the role of fluorescent optical sensors, focusing on their strengths and weaknesses, for CGT manufacture. The review concludes by discussing how the integration of CGT manufacture and fluorescent optical sensors could augment future bioprocessing approaches.